THE INFLUENCE OF HEDONIC SHOPPING MOTIVATION ON IMPULSE BUYING AMONG LAZADA CONSUMERS (A CASE STUDY ON STUDENTS OF THE MANAGEMENT DEPARTMENT, FACULTY OF ECONOMICS AND BUSINESS, HALU OLEO UNIVERSITY, KENDARI) - Azis Muthalib, Dzulfikri; Conny, Conny (Journal Economics Technology And Entrepreneur, 2025)
This study aims to examine and analyze The Influence of Hedonic Shopping Motivation on Impulse Buying Among Lazada Consumers (A Case Study of Students in the Management Department, Faculty of Economics and Business, Halu Oleo University, Kendari). The sample was selected using purposive sampling, with a total of 85 respondents. This research employed simple linear regression analysis. The results revealed that hedonic shopping motivation has a positive and significant effect on impulse buying behavior among consumers using the Lazada platform. An increase in hedonic shopping motivation is clearly linked to a corresponding rise in impulse buying behavior. These findings suggest that strong hedonic shopping motivation plays a critical role in driving impulsive purchasing tendencies among Lazada users.